Studies in law, politics, and society - Sarat, Austin (Bingley : Emerald Publishing Limited, 2017)
Studies in Law, Politics, and Society provides a vehicle for the publication of scholarly articles within the broad parameters of interdisciplinary legal scholarship. In this latest edition of this highly successful research series, articles examine a diverse range of legal issues and their impact on and intersections with society. Topics covered include: an analysis of Charles Reznikoff's autobiography and its implications for residential lease law; a classification of condominium crime; an historical and developmental account of judicial activism; a reconceptualization of the legal approach to the reproductive rights of adolescents; an examination of the stories told by foster care youth to legislatures, courts and policymakers; an account of the role of maturity, policy, and parental authority in legal standards for minors' rights; and the debate surrounding transgender children and teaching gender identity in schools. This volume brings together leading scholars and will be vital reading for all those researching in this subject area.
Prelims -- Commercial leases and family realities in Charles Reznikoff's family chronicle -- Condo crimes and legal prospects for confronting the unusual suspects -- The nursery years of'judicial activism' : from a historian's shorthand to media catchphrase 1947-1962 -- Teenage pregnancy, parenting, and abortion : legal limits on adolescents' reproductive rights --'Letting kids be kids' : youth voice and activism to reform foster care and promote'normalcy' -- Teen health care decisions : how maturity and social policy affect four hard cases -- Transgender children, teaching early acceptance, and the heckler's veto.
Keywords: Sociological jurisprudence; Law -- Political aspects; Political sociology; Law, Jurisprudence; Law & society